On determining the mechanical nociceptive threshold in pigs: a reliability study - Rettore Andreis, Felipe; Mørch, Carsten Dahl; Jensen, Winnie; Meijs, Suzan (Frontiers in Pain Research, 2023)
Background: A pressure algometer is a valuable tool for assessing the mechanical nociceptive threshold (MNT) in clinical pain studies. Recent research has turned to large animal models of pain because of the closer anatomy and physiology to humans. Although the reliability and usefulness of the MNT have been extensively validated in humans, similar data from large animals is still sparse. Objective: Therefore, the aim of the current study was to evaluate the reliability (within- and between-session) of MNT in the forelimb of pigs using a pressure algometer. Methods: Nine animals were used (23 – 40 kg), and MNTs were measured at both the right and left limbs at three different sessions, with three repetitions per session. The intraclass correlation coefficient (ICC) was used as a metric for relative reliability. The standard error of measurement (SEM) and coefficient of variation (CV) was used to assess absolute reliability. Systematic bias was also evaluated. Results: The average ICC was found to be 0.71 and 0.45 for the between-session and within-session, respectively. CV ranged from 17.9% to 20.5%, with a grand average of 19.1%. The grand average SEM was 249.5 kPa (16.6%). No systematic differences were found for the MNT between sessions, which suggests that there was no habituation to the stimulus. Conclusion: The reliability indices obtained in this study are comparable to results obtained in other species or anatomical regions and substantiate the use of the pressure algometer as a valuable tool to investigate the nociceptive system in pigs and translation to the human nociceptive withdrawal reflex.